Comparison of black scholes and garch models using collar strategy as a hedging efforts in the telecommunication industry (Telkomsel, XL, Indosat) - Sitepu, Victor Bastanta; Soma, Abdul Mukti (Journal of Multidisciplinary Academic and Practice Studies, 2024)
Purpose: This study aims to examine the influence of the internal control system and human resource competence on the quality of financial reports within the Nabire Regency Government. Research/methodology: A quantitative approach was employed using primary data collected through questionnaires distributed to 30 respondents working in financial administration across various regional apparatus organizations (OPD) in Nabire. The data were analyzed using multiple linear regression with SPSS to test the hypotheses regarding the direct effects of internal control and HR competence on report quality. Results: The results indicate that both the internal control system and the competence of human resources have significant positive effects on the quality of financial reporting. The better the internal control mechanisms and the higher the HR competence, the more reliable, accurate, and transparent the financial reports produced by the local government. Conclusions: Strengthening internal controls and enhancing HR competence are essential strategies for improving the quality of local government financial reports, ensuring better public accountability and compliance with reporting standards. Limitations: The study is limited by its small sample size and focus on a single regency, which may restrict the generalizability of findings to other regions or government levels. Contribution: This research contributes to public sector accounting literature by empirically demonstrating how governance and human capital factors influence financial reporting quality in local governments, offering insights for policymakers and practitioners aiming to enhance financial transparency.